PENINGKATAN TEKNIK LOMPAT JAUH MELALUI METODE KONVENSIONAL PADA SISWA KELAS X.TK.1 DI SMK NEGERI 6 MAKASSAR - Amahoru, Nurul Musfira; Ad'dien, Ad'dien; Jamaluddin, Jamaluddin (UNIVERSITAS NEGERI MAKASSAR, 2018)
This study aims to improve the long jump technique through conventional methods. This research is action research. The research subjects were students of class X.TK.1 at SMK Negeri 6 Makassar, which consisted of 30 female students and the analysis technique used was qualitative descriptive analysis. Based on the results of the recapitulation between cycles after the implementation of conventional methods in the second cycle shows that the long jump technique in students of class X.TK.1 in SMK Negeri 6 Makassar has an increase, it is shown from the results in cycle I there are 6 students (20.0% ) on a scale of 4 (good) and increased to 12 students (40.0%), so that an increase of 20.0% (40.0% - 20.0%). Likewise on the value scale 3 (medium category) shows that in the first cycle there were 7 students (23.3%) and increased to 18 students (60.0%) so that there was an increase of 36.7% (60.0% - 23, 3%). Thus it can be concluded that through the conventional method carried out in the second cycle had an increase of 56.7% (20.0% + 36.7%) in the long jump technique in students of class X.TK.1 at the SMK Negeri 6 Makassar. The results of the study concluded that: there was an increase in the long jump technique through conventional methods in class X.TK.1 students at Makassar State Vocational High School 6.